Analisis Strategi Promosi Dengan Paket Sembako Pada 212 Mart Kayuagung Untuk Survive Selama Masa Pandemi Covid - Reny Moulisa Ananda; Hilda Hilda; Mail Hilian Batin (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Micro, Small and Medium Enterprises are productive businesses engaged in commerce and are engaged in entrepreneurship. MSME themselves can be managed by individuals or business entities, where the business belongs to the criteria of a small or micro scope. In 1998, small or medium enterprises can compete with large companies. Because most small or medium businesses do not depend on loans or large capital. Promotion is an element in a company's marketing mix that is used to inform, persuade, and remind products of a company. Promotional mix is a combination of face-to-face selling advertising, sales promotion, publicity, public relations that helps achieve company goals. This study uses a qualitative approach with descriptive analysis method. The object of this research is 212 Mart Kayuagung. This study uses primary data and secondary data with data collection techniques of observation, interviews, and documentation. By using triangulation data collection techniques. 212 Mart Kayuagung in promoting its products, namely Advertising using banners, Personal Selling using face to face, Publicity using.